Molecular network using molecular circuit for drug delivery use - Narongchai Moongfangklang; Somsak Mitatha; Surasak Pipatsart; Preecha P. Yupapin (My University, 2012)
A novel design of molecular networks for drug delivery application using a PANDA ring resonator is proposed. By using the intense optical vortices generated within the PANDA ring resonator, the required molecules can be trapped and moved (transported) dynamically within the wavelength router and bus networks, in which the required drug delivery can perform within the wavelength router before reaching the required destination. PANDA ring is a modified optical add/drop filter. It is a name of Chinese bear, which is used to name the device by the authors. The advantage of the proposed system is that the drug delivery networks can perform within the tiny system (thin film device), where the large molecular drug networks such as ring, star and bus networks are also proposed, in which the applications such as Alzheimers’ and Parkinson diagnosis, blood circulation networks and in situ surgery operation are discussed.
Keywords: Genetic Neurodegenerative Diseases